2010
DOI: 10.1103/physrevc.81.015801
|View full text |Cite
|
Sign up to set email alerts
|

Stellar(n,γ)cross sections ofp-process isotopes Part I:

Abstract: We have investigated the (n, γ) cross sections of p-process isotopes with the activation technique. The measurements were carried out at the Karlsruhe Van de Graaff accelerator using the 7 Li(p, n)7 Be source for simulating a Maxwellian neutron distribution of kT = 25 keV. I. INTRODUCTIONAstrophysical models can explain the origin of most nuclei beyond the iron group by a combination of processes involving neutron captures on long (s-process) or short (r-process) time scales [1,2].However, 32 proton-rich stab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Approaches for the determination of reliable particle-nucleus potentials as well as a systematic study of (γ,n) reaction rates were shown. An interesting approach is also to use neutron-capture reactions for the determination of (γ,n) cross sections as shown in [37,38]. However, the most interesting reactions concerning the production of the heavy p nuclei involve unstable nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Approaches for the determination of reliable particle-nucleus potentials as well as a systematic study of (γ,n) reaction rates were shown. An interesting approach is also to use neutron-capture reactions for the determination of (γ,n) cross sections as shown in [37,38]. However, the most interesting reactions concerning the production of the heavy p nuclei involve unstable nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…The reverse process, i.e., (n, γ) reactions may serve the purpose. For example, Dillmann et al [3] studied a number of (n, γ) reactions with neutrons from the 7 Li(p, n) 7 Be reaction to simulate a Maxwellian neutron distribution at 25 keV thermal energy. Neutron capture reactions have been studied in various methods.…”
Section: Introductionmentioning
confidence: 99%
“…This is depicted in Fig. 4 for the Maxwellian average cross sections compiled recently [44] for E n = 30 keV. An essential feature here is our global ansatz for the spreading width which fixes the important tail of the E1-resonance; it depends on the IVGDR pole energies only and their dependence on exact deformation parameters is nearly unimportant.…”
Section: Photon Strength and Neutron Capturementioning
confidence: 98%